SHARIA AND HUMAN RIGHTS COMPATIBILITY IN DETERMINING THE AGE OF MARRIAGE IN INDONESIA - Suwardiyati, Rumi; Rohmah, Siti; Galib, Andi Muhammad; Halim, Abdul (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research aims to examine the interpretation of constitutional judges regarding the age limit for marriage, which is considered to contain compatibility and efforts to harmonize sharia and human rights principles in their decisions. This is motivated by child marriage tends to ignore the rights of children and women. Unfortunately, religious understanding and even state law often affirmed this practice. The research method used is normative juridical using secondary data. This research will analyze Constitutional Court Decision Number 22/PUU-XV/2017. This research will show the conflict between the interpretation of sharia -which has been the authoritative area of religious leaders- and the principles of Human Rights (HAM). Meanwhile, the interpretation of the judges of the Constitutional Court seems to contain discourse on the compatibility and harmony of sharia and human rights. This research reflects the Constitutional Court's approach and the petitioners' strategy to review the constitutionality of the minimum age for marriage as stated in the Marriage Law. The various approaches and arguments show that the applicant made a strategic decision by breaking a patriarchal culture and injustice before the Constitutional Court.